A systematic review on the diagnosis of pediatric bacterial pneumonia: when gold is bronze. - Tim Lynch; Liza Bialy; James D Kellner; Martin H Osmond; Terry P Klassen; Tamara Durec; Robin Leicht; David W Johnson (PLoS ONE, 2010)
Background In developing countries, pneumonia is one of the leading causes of death in children under five years of age and hence timely and accurate diagnosis is critical. In North America, pneumonia is also a common source of childhood morbidity and occasionally mortality. Clinicians traditionally have used the chest radiograph as the gold standard in the diagnosis of pneumonia, but they are becoming increasingly aware that it is not ideal. Numerous studies have shown that chest radiography findings lack precision in defining the etiology of childhood pneumonia. There is no single test that reliably distinguishes bacterial from non-bacterial causes. These factors have resulted in clinicians historically using a combination of physical signs and chest radiographs as a 'gold standard', though this combination of tests has been shown to be imperfect for diagnosis and assigning treatment. The objectives of this systematic review are to: 1) identify and categorize studies that have used single or multiple tests as a gold standard for assessing accuracy of other tests, and 2) given the 'gold standard' used, determine the accuracy of these other tests for diagnosing childhood bacterial pneumonia. Methods and findings Search strategies were developed using a combination of subject headings and keywords adapted for 18 electronic bibliographic databases from inception to May 2008. Published studies were included if they: 1) included children one month to 18 years of age, 2) provided sufficient data regarding diagnostic accuracy to construct a 2x2 table, and 3) assessed the accuracy of one or more index tests as compared with other test(s) used as a 'gold standard'. The literature search revealed 5,989 references of which 256 were screened for inclusion, resulting in 25 studies that satisfied all inclusion criteria. The studies examined a range of bacterium types and assessed the accuracy of several combinations of diagnostic tests. Eleven different gold standards were studied in the 25 included studies. Criterion validity was calculated for fourteen different index tests using eleven different gold standards. The most common gold standard utilized was blood culture tests used in six studies. Fourteen different tests were measured as index tests. PCT was the most common measured in five studies each with a different gold standard. Conclusions We have found that studies assessing the diagnostic accuracy of clinical, radiological, and laboratory tests for bacterial childhood pneumonia have used a heterogeneous group of gold standards, and found, at least in part because of this, that index tests have widely different accuracies. These findings highlight the need for identifying a widely accepted gold standard for diagnosis of bacterial pneumonia in children.